Endogenous and Exogenous Elemental Speciation in Human Hair by Various Washing Procedures and Determination by Flame and Electrothermal Atomic Absorption Spectrometry - SABER-TEHRANI, M.; TADAYON, F. (Asian Journal of Chemistry, 2010)
Human hair is a suitable biomarker for determination of trace elements absorbed into the body. However, it is necessary to differentiate between the part which is adsorbed on the hair from environment (exogenous) and that part originated from the body of the host (endogenous). Hence to remove exogenous elements the hair sample must be washed before digestion. In the present work, scalp human hair was exposed to sweat, spiked with certain trace elements and then washed with different solutions to desorb the adsorbed elements. Investigations of 10 various washing procedures to remove external contaminants show that in exposed hair samples cadmium, cobalt, copper, iron, nickel and zinc are significantly removed from hair using a 1 % (w/v) sodium diethyl-dithiocarbamate (DDTC) wash, with 77, 35, 79, 40, 41 and 70 %, respectively being washed-off. The removal of nickel and zinc from exposed hair is, however, more efficient with 0.1M HCl, with 65 and 78 % of each element, respectively being washed-off. After determination of the desorbed elements, the washed hair samples were digested in a mixture of HNO3 and H2O2, for the determination of endogenous elements. Both the exogenous and endogenous elements were determined by ELAAS or FAAS. In order to show the effective removal of adsorbed elements, the trace elements content of hairs of two groups of people were determined, living in a village and our test group were mine workers.